2012
DOI: 10.2478/s11772-012-0034-x
|View full text |Cite
|
Sign up to set email alerts
|

Selected polymers on CW and pulsed THz investigations

Abstract: The paper gives the results of refractive indexes for three plastic materials: polyethylene, polymethyl methacrylate and polyvinyl chloride, which are measured and compared in two arrangements - a CW THz photomixer and a pulsed THz spectrometer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
2
0
0
Order By: Relevance
“…2(c) tends to decrease slightly when the frequency increases, our data is more consistent with the data in Ref. 27. Looking at the data in Figs.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…2(c) tends to decrease slightly when the frequency increases, our data is more consistent with the data in Ref. 27. Looking at the data in Figs.…”
Section: Resultssupporting
confidence: 92%
“…It has been reported that the refractive index at around 250 GHz for PMMA is about 1.6 or a little larger than 1.6, 13,26) and the refractive index at 200 GHz for PMMA is 1.474. 27) Because the refractive index of pure PMMA in Fig. 2(c) tends to decrease slightly when the frequency increases, our data is more consistent with the data in Ref.…”
Section: Resultssupporting
confidence: 91%